Comparison of forehead infrared thermometry with axillary digital thermometry in detecting neonatal hypothermia & study of effects of early breast feeding and adequate clothing in maintaining neonatal temperature - Dr.Virendra Kurrey; Dr. Madhavi Sao; Dr. Sharja Phuljhele (Pediatric Review: International Journal of Pediatric Research, 2019)
Background: Neonatal hypothermia is a well-recognized important contributing factor to neonatal morbidity and mortality especially in developing countries. Axillary thermometry is the conventionalmethod in neonates to measure body temperature. Forehead-infrared thermometry is new non-touch method that may reduce infection rate and discomfort of neonates. Objectives: To compare the accuracy of forehead infrared thermometry with axillary digital thermometry in detecting neonatal hypothermia and to determine the association of inadequate clothes and delayed initiation of breastfeeding with increased risk of hypothermia. Materials and Methods: A cross-sectional study was conducted among term neonates with age < 24 hrs of life in the postnatal wards of tertiary care hospital. The body temperature of neonates was measured by both methods & their accuracy was analyzed to detect hypothermia with the adequate statistical method. Association between delayed breastfeeding and inadequate clothing with neonatal hypothermia were also evaluated. Result: Mean difference (bias) of the axillary and infrared forehead readings (-0.29°C) in the morning and (-0.31°C) in the evening. Agreement by the Bland-Altman method in the morning (-0.76 & 1.33) and at evening (-1.33 & 0.76) shows the transference of two techniques was inappropriate indicating that infrared-thermometry cannot replace axillary digital thermometry. Subjects who were early breastfed and with adequate clothing were found to have significantly higher body temperature. Conclusion: Forehead infrared thermometry cannot replace axillary thermometry and is not recommended for neonatal temperature measurement. Early breastfeeding, covering of heads, as well as extremities, were found to be protective from hypothermia.